Reasons of Banning Smoking in Private Vehicles - Precioso, José (2018)
The fine particulate matter present in environmental tobacco smoke (ETS), also known as PM2.5 (inhalable or ‘breathable’ particulate matter with a diameter of ≤2.5μm), can be inhaled and deposited deep into the lungs, damaging them, and are, therefore, considered hazardous to human health. The amount of this particulate matter present in cars varies depending on the characteristics of the vehicle, such as the position of the windows, the ventilation/air conditioning levels and the speed as well as the number of cigarettes smoked in the cabin. A study measuring the level of hazardous particulate matter in an car while someone was smoking revealed that it is similar to the level of particulate matter found in a bar where smoking is allowed. Motor vehicles are microenvironments where passen-gers may be exposed to high concentrations of ETS if someone smokes in the car.